The thermal decomposition kinetics of [Co(bipy)(H2O)4](C4H4O4) • 4H2O - Yakuphanoğlu, Fahrettin; Ying, SM (Walter de Gruyter Gmbh, 2005)
The thermal decomposition kinetics of [Co(bipy)(H2O)(4)](C4H4O4) center dot 4H(2)O was carried out by thermogravimetry (TG) and derivate thermogravimetry (DTG) analysis at four heating rates of 5, 8, 11 and 14 degrees C/min in nitrogen atmosphere. TG confirmed that thermal decomposition of the compound takes place in a single step. The kinetic parameters (activation energy, frequency factor, and activation entropy) were calculated using various forms of non-isothermal methods. The activation energy obtained by the Ozawa method is in agreement with the value determined by the Coats-Redfern technique. However, a much lower activation energy was obtained by the Kissinger method.
Keywords: thermal analysis; metal complex; kinetic parameters